Kritik Globalisasi: Fenomena Fast Fashion Sebagai Budaya Konsumerisme Pada Kalangan Pemuda Kota Surabaya - Lukmanul Hakim, Adiyaksa; Rusadi, Emmy Yuniarti (AL MA'ARIEF : Jurnal Pendidikan Sosial dan Budaya, 2022)
Fast fashion is a concept implemented by clothing retailers, where the direction and strategic goals of the business follow the latest trends with the best response to consumer demand through price. The fast fashion system itself is a system formed because of globalization, and this is what will lead to a culture of consumerism among youth. This study aims to examine globalization’s criticism of fast fashion among Surabaya youth, the causes of Surabaya City youth interested in fast fashion, and solutions to overcome fast fashion, which causes a consumerist culture among Surabaya City youth. This type of research is descriptive qualitative research. The data collection technique in this study used questionnaires directly, then the data used in this study used primary data while data analysis was carried out using content analysis techniques. Based on the results of the study, it was found that the phenomenon of fast fashion for the youth of Surabaya City led to a culture of consumerism. To reduce the pattern of consumerism, it must be instilled in young people about what things to buy according to needs, not a desire because from this desire arises a passionate desire to style according to trends.